1996
DOI: 10.1139/e96-111
|View full text |Cite
|
Sign up to set email alerts
|

The paleoecological significance of new species of Limbicysta (Acritarcha) from the upper Albian of the Canadian Arctic Islands

Abstract: Umbicysta octopedifomis and Limbicysta quadriformis are new acritarch species from the upper Aibian Bastion Ridge and Strand Fiord formations of the Sverdrup Basin, Canadian Arctic Islands. They are similar to the type species, Limbicysta pediformis Marshall, but have eight asymmetric or four symmetric process tips versus the four asymmetric and one symmetric process tips of L, pediformis. They are distinguished from other species of Limbicysta by their single wall layer, lack of longitudinal folds, and degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…The Kingittoq Member, dated as Cenomanian is characterised by common to abundant Rugubivesiculites rugosus pollen. MacRae et al (1996) reported a similar assemblage from the suggested upper Albian or younger, uppermost Bastion Ridge and Strand Fiord formations in Arctic Canada. The brackish water interval is characterised by the presence of Limbicysta octopediformis, Luxadinium spp., Nyktericysta arachnion, Quantouendinium sp., Wuroia sp., and the alga Tetraporina.…”
Section: South Coast Of Nuussuaqmentioning
confidence: 63%
See 3 more Smart Citations
“…The Kingittoq Member, dated as Cenomanian is characterised by common to abundant Rugubivesiculites rugosus pollen. MacRae et al (1996) reported a similar assemblage from the suggested upper Albian or younger, uppermost Bastion Ridge and Strand Fiord formations in Arctic Canada. The brackish water interval is characterised by the presence of Limbicysta octopediformis, Luxadinium spp., Nyktericysta arachnion, Quantouendinium sp., Wuroia sp., and the alga Tetraporina.…”
Section: South Coast Of Nuussuaqmentioning
confidence: 63%
“…The dinocyst assemblage is only represented by the brackish water genera Balmula, Nyktericysta, Pseudoceratium, and Vesperopsis, originally described from fluvial to estuarine deposits of early late Albian age of the Western Interior, USA (Bint, 1986) and later reported from brackish water deposits of Albian age from eastern Canada (Zippi, 1998) and late Albian age from Arctic Canada (MacRae et al, 1996). Nøhr-Hansen and McIntyre (1998) recorded few Nyktericysta davisii and Psedoceratium interiorense, together with marine dinocysts of late middle Albian age, from Axel Heiberg Island, Arctic Canada.…”
Section: Paleontologymentioning
confidence: 99%
See 2 more Smart Citations
“…The outline of Fig. 3 MPFZ -Mitchell Point Fault Zone, PBF -Petersen Bay Fault, PI -Phillips Inlet, WIC -Wootton Intrusive Complex, YB -Yelverton Bay. and sanidine data, MacRae et al, 1996), of 102.5 ± 2.6 Ma (whole-rock age, Estrada & Henjes-Kunst, 2013) and of 95.3 ± 0.4 Ma (whole-rock age, Tarduno et al, 1998) were reported for the Strand Fiord Formation. Basalts within the stratigraphically equivalent Hassel Formation are exposed on northern Amund Ringnes Island (Balkwill, 1983), Ellef Ringnes Island (Evenchick et al, 2015), and northeast Ellesmere Island (Embry & Osadetz, 1988;Osadetz & Moore 1988).…”
Section: Geological Overview Of the Northeast Canadian Arcticmentioning
confidence: 96%